MANIFESTATION OF PSYCHOSOCIAL BEHAVIORAL MISADJUSTMENT AS INDICATORS OF MENTAL HEALTH IN STUDENTS AT THE URP - SÁNCHEZ-CARLESSI, Héctor (2024)
The university stage demands academic demands that provoke maladjusted behavior in students, considering them as difficult or threatening situations. Therefore, the study focuses on undergraduate students at the Ricardo Palma University, in order to find the significant differences between the faculty, the year of admission and sex compared to the Stress, Anxiety, Depression, Uncertainty and Desirability scales. Social of the INDACPS-N 2022 questionnaire, applied to a sample of 533 participants. The results show that there are significant differences between the Stress and Depression Scale, and the Faculty (p<0.05). On the other hand, entrants from 2017 to 2021 presented a high category of maladjusted behavior compared to entrants from 1988 to 2016. Likewise, men present scores between low and medium, while women have scores between medium and high in the Stress, Anxiety, Depression and Uncertainty Scales. It is concluded that the sampleexperiences high or very high levels of stress (49.91%), anxiety (34.15%) and depression (29.08%), and manifest uncertainty (36.96%) between ranges of high and very high scores; and social desirability (67.54%).